Diverse domains of THREAD/DIAP1 are required to inhibit apoptosis induced by REAPER and HID in Drosophila. - Lisi, S (2000)
Significant amounts of apoptosis take place during Drosophila development. The proapoptotic genes reaper (rpr), grim, and head involution defective (hid) are required for virtually all embryonic apoptosis. The proteins encoded by these genes share a short region of homology at their amino termini. The Drosophila IAP homolog THREAD/DIAP1 (TH/DIAP1), encoded by the thread (th) gene, negatively regulates apoptosis during development. It has been proposed that RPR, GRIM, and HID induce apoptosis by binding and inactivating TH/DIAP1. The region of homology between the three proapoptotic proteins has been proposed to bind to the conserved BIR2 domain of TH/DIAP1. Here, we present an analysis of loss-of-function and gain-of-function alleles of th, which indicates that additional domains of TH/DIAP1 are necessary for its ability to inhibit death induced by RPR, GRIM, and HID. In addition, that analysis of loss-of-function mutations demonstrates that th is necessary to block apoptosis very early in embryonic development. This may reflect a requirement to block maternally provided RPR and HID, or it may indicate another function of the TH/DIAP1 protein.